2021
DOI: 10.1371/journal.pone.0249461
|View full text |Cite
|
Sign up to set email alerts
|

Normative values of the vibration perception thresholds at finger pulps and metatarsal heads in healthy adults

Abstract: Aims To establish normative values of vibration perception thresholds (VPTs), using multi-frequency vibrometry at finger pulps and at metatarsal heads of the foot in healthy adults. We also aimed to investigate factors that could potentially affect VPTs such as age, sex, height, weight, foot- or handedness and skin temperature. Methods VPTs were examined in 924 healthy and randomly selected subjects in the southern Sweden (mean 46 years; 628 women and 296 men). Inclusion criterias were adult subjects (>18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 44 publications
2
29
0
1
Order By: Relevance
“…A study by Ekman et al on normative values of vibration perception thresholds shows that the thresholds deteriorate every year, as is expected considering the impact of ageing on neuronal health 37 . However, Ekman et al show that the deterioration is small with only one year of aging, in both upper and lower extremities, while clearer changes in vibration perception thresholds can be seen over a longer aging period, for example 10 years 37 . Moreover, in this study, the nerve function of the upper extremity, analysed in the ulnar nerve not affected by any nerve compression lesion, did not differ between type 2 diabetes and healthy controls.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…A study by Ekman et al on normative values of vibration perception thresholds shows that the thresholds deteriorate every year, as is expected considering the impact of ageing on neuronal health 37 . However, Ekman et al show that the deterioration is small with only one year of aging, in both upper and lower extremities, while clearer changes in vibration perception thresholds can be seen over a longer aging period, for example 10 years 37 . Moreover, in this study, the nerve function of the upper extremity, analysed in the ulnar nerve not affected by any nerve compression lesion, did not differ between type 2 diabetes and healthy controls.…”
Section: Discussionmentioning
confidence: 63%
“…We strongly believe that this age difference, of in median 2 years, will not impact the results in a cohort of participants around 70 years of age. A study by Ekman et al on normative values of vibration perception thresholds shows that the thresholds deteriorate every year, as is expected considering the impact of ageing on neuronal health 37 . However, Ekman et al show that the deterioration is small with only one year of aging, in both upper and lower extremities, while clearer changes in vibration perception thresholds can be seen over a longer aging period, for example 10 years 37 .…”
Section: Discussionmentioning
confidence: 88%
“…The examination of the vibration perception can be useful to detect diabetic peripheral sensory neuropathy at an early stage, and it can be easily assessed by a 128 Hz tuning fork (54). Normative values of vibration perception thresholds in finger pulps and metatarsal heads have been published in healthy children and adolescents (62) and in adults (63). A recent study by Abraham et al (64) found impaired vibration perception both in the fingers and in the toes among patients with type 1 and type 2 diabetes mellitus; however, the difference was significant only in the toes compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-frequency vibrometry was performed at baseline. All evaluations and follow-up visits used the VibroSense Meter ® II (Vibrosense Dynamics AB, Malmö, Sweden)—a CE-marked Class I medical device licensed to measure vibration perception thresholds (VPTs) between 4 and 500 Hz within a pre-specified skin temperature—and an applied pressure range [ 12 , 31 ]. VPTs were measured at 32, 125, and 250 Hz on the tactile surface of the finger pulp of the index (referred to as DigII-32 Hz, DigII-125 Hz, and DigII-250 Hz) and little finger (DigV-32 Hz, DigV-125 Hz, and DigV-250 Hz) on the patient’s dominant hand, and VPTs at 8, 32, and 125 Hz on the palmar skin of the first (MT-I-8 Hz, MT-I-32 Hz, and MT-I-125 Hz) and fifth metatarsal head (MT-V-8 Hz, MT-V-32 Hz, and MT-V-125 Hz) of the patient’s dominant foot [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Multi-frequency vibrometry (MF-V) is a novel semiquantitative psychophysiological measurement that captures multiple vibration perception thresholds (VPTs) from tactile non-glabrous skin [ 12 ]. Low-frequency MF-V has shown promise in early subclinical detection of diabetic neuropathy, linking measurements to worse glycemic control [ 13 ] and also showing a strong association with the risk of developing diabetic ulcers [ 14 ].…”
Section: Introductionmentioning
confidence: 99%